Students' Perceptions of Social Media Confidence Versus Classroom Social Anxiety - Telaumbanua, Yasminar Amaerita; Harefa, Wina Anjelina; Gea, Tri Yanti Nibenia; Laoli, Okta Cristopher; Gulo, Neni Suryani; Hulu, Lince Kristi (Universitas Muhammadiyah Gresik, 2024)
The rise of social media has transformed communication and self-expression, but it has also created a disparity between online and offline personas, particularly among college students. This study investigates the phenomenon of social media confidence versus classroom social anxiety at University of Nias, focusing on second- and fourth-semester students in the English education department. Using a qualitative phenomenological approach, in-depth interviews were conducted with five students who actively use social media but interact less in the campus environment. Thematic analysis of the interviews revealed that students experience was higher confidence and satisfaction on social media due to the lack of direct pressure and anonymity, which contrasts with their anxiety in traditional classroom settings. The study highlights the importance of a supportive and inclusive classroom environment to reduce social anxiety and enhance student engagement. Universities should provide resources such as psychological counseling, social skills training, and support groups to help students manage social anxiety. Integrating social media into the learning process and encouraging a balance between online and offline interactions can foster student confidence in both contexts. Effective anxiety management training is also essential for helping students navigate social dynamics in classrooms and on social media. These findings can inform interventions and strategies to support students in developing a healthy sense of self-presentation and authentic connections across different social spheres.